Pelestarian Bangunan Arsitektural Kolonial Belanda di Kawasan Kotabaru, Yogyakarta - Ahmad Aguswin; Akhmad Akromusyuhada (Jurnal Pelita Teknologi, 2021)
This study aims to identify building characteristics from architectural periodization based on physical appearance and visual appearance on a micro (regional) scale in the Kotabaru area, Yogyakarta. This area is part of the City of Yogyakarta which developed the concept of Planned Development City in several cities in Indonesia which had functions and roles in the structure of the Dutch colonial government. Furthermore, the characteristics of this building become a reference for preserving colonial buildings as a form of building conservation based on the classification results of type, structure, and condition of the building. The method used in this study is descriptive-qualitative, with components forming the visual appearance of the area as the unit of analysis. The visual appearance of the area is analyzed within the scope of the area (urban space) with a typological approach to buildings and urban spaces designed by Karstens in the Kotabaru area. The building facade as one of the components forming the visual appearance is discussed as a unitary mass and the shape of the building that forms the urban corridor wall in the Kotabaru area.